Instituições e cooperação social em Douglass North e nos intérpretes weberianos do atraso brasileiro - Aguilar Filho, Hélio Afonso de; Fonseca, Pedro Cezar Dutra (Estudos Econômicos (São Paulo), 2011)
The paper aims to rescue the theoretical approach of the institutional framework of Douglass North and the arguments used by interpreters of Brazil recognized Weber's guidance, as Sérgio Buarque de Holanda, Vianna Moog and Raymundo Faoro. To this end, highlights the understanding of the relationship between institutions and social cooperation in the works of these authors as a relevant variable to explain the long-term performance of the Brazilian economy and its relative backwardness.